Ricardian Equivalence and National Saving in the United States. (IMF Working Papers; Working Paper, 1988)
This paper examines the relative efficacy of cuts in government spending on goods and services and increases in taxation as tools for augmenting national saving--an issue related to Ricardian equivalence. The theoretical analysis shows little presumption in favor of spending cuts for this purpose and suggests that the issue is ultimately empirical. The empirical work for the United States suggests behavior close to zero Ricardian equivalence. Consequently, while there may be other reasons for favoring one approach or the other, cuts in government spending and increases in taxation appear broadly equivalent in terms of their impact on national saving.